Student Perspectives on the Importance of Digital Security Technology in Higher Education - Muh. Alwan Prawira; Khaerul Hidayat Z; Andi Dio Nurul Awalia; Dian Puspita Sari Andri (Sakura Digital Nusantara, 2025)
The dependence on digital technology in higher education has increased the need for digital security technology. This study aims to explore students' perspectives on the importance of digital security in Indonesian higher education, focusing on factors such as motivation, behavior, trust, and intention to use digital security technology. Using a quantitative descriptive approach and cross-sectional design, data were collected from 91 respondents through a Likert scale questionnaire covering the variables of Motivation and Behavior, Perceived Trust, Electronic Word of Mouth, Actual Use, and Intention to Use. The results show that students have high motivation and positive behavior towards the use of digital security technology, supported by their trust in the effectiveness of the technology and the role of the government. These findings indicate that the adoption of digital security technology can be strengthened through better digital security education and literacy, as well as supportive policies. This research contributes theoretically to the literature on technology acceptance in higher education and offers practical insights for increasing student awareness and participation in digital security.